THE EFFECT OF VARIATION OF VOLUME SOLUTION OF WULUH STRAWELL AND KEY ORANGE SITE ON PH VALUE, ELECTRICAL PROPERTIES AND CHANGES IN ELECTRODE MASS - Zafira Amalia Nasution; ratni sirait; abdul halim daulay (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2021)
Research has been carried out on "The effect of increasing the volume of the solution of star fruit juice and key orange juice on the pH value, electrical properties and changes in electrode mass". This study aims to determine the effect of volume variations of starfruit juice and key oranges (0%:100%, 25%:75%, 50%:50%, 75%:25% and 100%:0%) on the pH value, voltage, current, and electric power, to determine the decrease in voltage and electric current due to the loading of the red LED lamp for 1 hour and to determine the change in the mass of the Cu-Zn electrode for 1 hour. This research was carried out with the working principle of a voltaic cell using a pair of Cu-Zn electrodes as anode and cathode connected in series. The measurement results obtained that the best sample variation is in the 100% variation of starfruit juice with a total volume of 300 ml resulting in the values of pH, voltage, current, and electric power of (2.2; 1.73 V; 1.05 mA, respectively). ; and 1.81 mW), while for the lowest sample variation, there is a variation of 100% key orange juice with a volume of 300 ml producing the values of pH, voltage, current, and electric power, respectively (2.8; 1.64 V; 0, 99 mA and 1.62 mW). The more variations in the volume of the key orange juice, the better the voltage, current and electric power. As for the test results, the loading of the red LED lights causes a decrease in voltage and electric current for 1 hour, so the longer the loading time, the dimmer the lights. Furthermore, for 1 hour the voltaic cell reaction took place, resulting in a change in the mass of the Cu-Zn electrode where the mass of the Cu electrode increased and Zn decreased. Keywords: Starfruit, key oranges, pH, electricity